Analysis of blood culture practices in multicenter university-affiliated hospitals in Korea: A retrospective study focused on procedural optimization - Sae Am Song; Sunggyun Park; Kwangsook Woo; Yu Kyung Kim; Jung-ah Kim; Sunjoo Kim (PLoS ONE, 2025)
Background Blood culture is an essential diagnostic tool for detecting bloodstream infections, particularly in patients with suspected sepsis. Routine implementation in healthcare settings necessitates adherence to standardized protocols to ensure diagnostic accuracy. We assessed blood culture practices in university-affiliated hospitals across Korea by analyzing key performance metrics and related indicators. Methods In 2024, a standardized questionnaire was distributed to 14 university-affiliated hospitals. The survey collected data on blood culture practices during 2023, including the total number of cultures performed, the number of sets obtained per episode, the frequency of repeated cultures, the volume of blood collected per bottle, discrepancies in culture results, the types of organisms isolated, and post-test reporting practices. Results In 2023, the median number of blood cultures requested per 1,000 hospitalized patients was 166.6 (43,699 cultures among 241,053 admissions). Two-set collections were most common (median 68.9%), followed by single-set collections (13.0%). Repeat cultures were more frequently performed following negative results (29.2%) than positive ones (5.5%). The median volume collected was 4.0 and 4.3 mL for aerobic and anaerobic bottles, respectively. Only 16.7% of Gram stain results were reported within 2 h. Conclusions Blood culture practices, particularly regarding test ordering and the use of two or more sets per episode, appear generally appropriate. However, specific aspects—including the indications for repeat cultures, adequacy of collected blood volume, and timeliness of Gram stain reporting—require further evaluation and targeted quality improvement efforts.